Environmental analytics of the water quality and sediment from Lake Vég of Ecséd - Grósz, János; Kruppiné Dr. Fekete, Ilona (JOURNAL OF LANDSCAPE ECOLOGY, 2016)
Our paper deals with the examinations of the water quality, the sediment and environmental analytics of lake Vég of Ecséd. Since 2007, We’ve sunk several times per yearly in the lake. The diving made us tor realize, that the technique enables the sampling of areas, which would normaly be impossible to reached, or would require a high amount of investment. The diving technique allows an in-depth and more detailed examination of the aquatic systems. The aim of the project was not only to define the environmental state of the lake Vég of Ecsed by instrumental analytic examinations, but also to decide if the water from Ágói brook has any effect on the lake; moreover, to compare the accuracies of on-site measurements and laboratory examinations. During the diving, the depth data of the lake bed were recorded by a diving computer, which enabled the 3D mapping of the lake bed. During the sampling sessions, 237 water samples were taken from the lake Vég. With the help of adiving equipment 6 sediment samples were brought up from different depths and 30 water samples were taken from Ágói brook in three different sampling sessions. A sediment analysis was carried out, where the element content of the samples were defined by using ICP OES. The water samples went through on-site measurements and chemical and physical measurements, and also ecotoxicology and laboratory examinations were carried ou.t. The results of the samplings from the lake showed that the water is contaminated by nitrite, nitrate and ammonium. The water of the lake, however, was proved to be excellent in terms of quality. The main reason of the brook being contaminated is that the sewerage of the precincts is not complete, which lead to the contamination of the underground water as well. The good environmental and ecological state of the lake is due to several factors. On one hand, the examination of the hidrologic and geologic data led to the realization that the water course is bordered by a lignite wall. The subsurface water, which feeds the lake, arrives to the lake through a carbon wall. This formation functions as a natural filter, and clears the water from polluting components. On the other hand, it is due to the strict rules of the usage of the lake, taken by its owner. He makes a great effort to cater for the lake. These actions make it possible to avoid, that pollution from inner sources get into the water. The care for the lake can be stated as a nation-wide example.
Keywords: environmental analytics; water quality; sediment analytics; environmental conditional